Extramedullary relapse of multiple myeloma presenting as a breast lump. Issue 3 (9th March 2021) - Seviar, Dale; AlshiekhAli, Zainab; Howlett, David
Abstract : Multiple myeloma (MM) involving the breast tissue is rare. We report the case of a 70-year-old woman with a background of previously treated MM in remission presenting with a breast lump. Histology showed a plasma cell neoplasm and subsequent staging investigations showed widespread extramedullary relapse of MM. Despite its rarity, this diagnosis should be considered within the differential diagnosis of breast masses as it can arise de novo or may be the first presenting feature of myeloma. The importance of the multidisciplinary team approach with triple assessment of the breast, as well as recent advances in knowledge regarding extramedullary disease in myeloma and novel treatment approaches in MM are discussed.